К вопросу о политике большевиков в деле установления контроля над высшей школой в 1920-х годах (на примере Петроградского медицинского института). - Алексеевич, Журавлёв Александр (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article is depicts the Soviet government’s policy on higher education on an example of the Petrograd medical institute. During the first decade Bolshevik’s policy has evolved, at first it had “Decree” character and has not affected the internal life of universities and institutes. In the mid1920s started the second phase, characterized by displacement of the old professors, admission of students on the class principle and the formation of the new Soviet intelligentsia. By the end of the 1920s, students became obedient media for the Bolsheviks, that allowed to completely abandon all of the higher school pre-revolutionary heritage.